Catálogo de las especies de equinodermos sl. del Ordovícico español. Catalogue of the echinoderms species s.l. of Spanish Ordovician - Arroyo, Fernando; Lara, Ricardo (Coloquios de Paleontología, 2002)
There are many works where the different species of echinoderms s.l.2 known for Spanish Ordovician have been picked up. The aim of this work is to complement those papers by picking up all the species cited for this period of time with a list as complete as possible of the different outcrops and the chronological range of each species. Besides, the mot significant references for each case have been included as well as the different valid synonims and the references that have been used. Moreover, it has been included a table with the chronological distribution of the different species and open taxonomy taxa, as a list of synonims and the name of the valid species nowadays.
Keywords: Echinoderms; Ordovician; Spain